Digitization and Digital Governance in India: With Special Refernce to Electronic Payment in Financial Sector - Kumari, Arunita; Saxena, Kavita (Journal of Commerce and Trade, 2019)
The introduction of technology in Payment and Settlement System has made a noticeable impact on banking services. It brought efficiency in banking services by making it speedier, cost effective, secure and accessible to its users. Use of electronic/digital payment products have increased electronic transactions and thereby promoted digitization. A period of twelve years, from year 2006 to year 2018 has been studied in this research paper to analyse the shift from paper to electronic/digital payment modes. Classification-JEL : O 23, O 33.